Investigation of the Effect of Small Hardening Spots Created on the Sample Surface by Laser Complex with Solid-State Laser - Nozdrina O. V. Olga Vladimirovna; Zykov I. Yu. Iliya Yurievich; Melnikov A. G. Alexander Grigorievich; Tsipilev V. P. Vladimir Papilovich; Turanov S. B. Sergey Borisovich (2018, 2018)
Title screen